A comparative study between early and conventional intestinal stoma closure in a tertiary care institute - Vatvani, Vijay; Khoja, Hanuman Ram; Krishna, Chappidi Vamsi; Rustagi, Saaransh; Jain, Richa (International Surgery Journal, 2024)
Background: Little is known about ideal time for stoma closure. Therefore, the aim of this study is to compare early versus conventional stoma closure following bowel surgery in terms of quality of life (QoL), length of hospital stay (LoH), and postoperative complications. Methods: This randomized controlled trial was conducted at a medical college affiliated teaching hospital from May 2023 to June 2024. The 116 patients undergoing bowel surgery with temporary stoma creation were randomized into early closure (3 weeks post-surgery) and conventional closure (8-12 weeks post-surgery) groups. Primary outcome was anastomotic leak rate. Secondary outcomes included other postoperative complications, LoH, and QoL assessed using the EORTC QLQ-C30 questionnaire. Results: There was no significant difference in anastomotic leak rates between early (6.9%) and conventional (12.1%) closure groups. Overall complication rates were similar (56.9% early vs 50% conventional). LoH did not differ significantly between groups. QoL scores were significantly higher in the early closure group, with 100% of patients achieving considerable improvement (EORTC score 26-36) compared to 79.3% in the conventional group (p<0.05). Conclusions: Early stoma closure is safe and feasible in appropriately selected patients, with no increased risk of anastomotic leak or other complications. It significantly improves QoL compared to conventional closure timing, without prolonging hospital stay. These findings suggest that early stoma closure may be a beneficial option for suitable patients following bowel surgery.